Phylogeny of the Eocene Antarctic Tapetinae Gray, 1851 (Bivalvia, Veneridae) from the la Meseta and Submeseta formations - Alvarez, Maximiliano Jorge; del Río, Claudia Julia (Journal of Paleontology)
Systematic analysis shows that the Southern Hemisphere bivalve genus Retrotapes includes the Antarctic species R. antarcticus, R. newtoni, and R. robustus and recognizes for the first time the presence of Katelysia represented by K. florentinoi. Two new genera were erected in this study: Marciachlys new genus to include M. inflata new combination, and Adelfia new genus, which includes A. austrolissa new combination and A. omega new species from the Eocene of Antarctica, and the late Eocene Chilean A. arenosa new combination. Eurhomalea carlosi was synonymized with K. florentinoi; Cyclorismina marwicki with R. antarcticus; Gomphina iheringi was considered an indeterminate species; and Cockburnia lunulifera was excluded from the Tapetinae. These systematic assignments are supported by a phylogenetic analysis, which recognizes an Austral clade of Tapetinae, comprising all the genera mentioned above, along with Marcia, Paleomarcia, Atamarcia, and Protapes. Fil: Alvarez, Maximiliano Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: del Río, Claudia Julia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina